Co-existence of mucin-producing urothelial-type adenocarcinoma of the prostate and inverted papilloma of the bladder - Mu, Xiao-Nan; Wang, Si-Jun; Sun, Zhi-Gang; Zhang, Min; Li, Zhe; Zhang, Long-Yang (Contemporary Oncology/Współczesna Onkologia, 2017)
Adenocarcinoma of prostate with mucinous differentiation arising in the male urethra is extremely rare, with only 21 cases reported in the previous literature. A diagnosis of mucin-producing urothelial carcinoma of the prostate is based on the pathology, immunohistochemistry, and clinical examination by excluding the secondary adenocarcinoma of the prostate. We present a case of unexpected mucinous urothelial carcinoma of prostate with co-existing inverted papilloma of bladder in a 57-year-old man. The patient underwent transurethral resection of the prostate (TURP) and transurethral resection of a bladder tumour (TUR-Bt), and the pathologic result showed mucinous prostate carcinoma and bladder inverted papilloma. Immunohistological stain was negative for prostate-specific antigen (PSA), prostate-specific acid phosphatase (PSAP), and P63, but positive for cytokeratin 7 (CK 7), CK 20, clone 34E12 and P504S. A complete endoscopic examination was performed to exclude the secondary adenocarcinoma of prostate. This case illustrates the clinical and pathological features of a rare and unexpected mucin-producing urothelial carcinoma of prostate in a bladder neoplasm patient.